Analisis Beban Mental Karyawan Menggunakan NASA-TLX pada Rooms Division Prime Plaza Hotel Kualanamu - Anshori, Mohamad Yusak; Meda Sulistyaningtyas, Febronia; Wahyuni, Khairi (JURNAL AKUNTANSI DAN MANAJEMEN, 2023)
This research aims to analyze the mental workload of Prime Plaza Hotel Kualanamuemployees and provide recommendations to management to overcome the decline in service qualitydue to workload. Data was taken from the Rooms Division which consists of the front officedepartment and housekeeping department with a total of 18 respondents from various levels ofpositions. The NASA-TLX method was used to process the data, and the results showed that theworkload in the Rooms Division was very high based on six indicators. This research aims tounderstand the level of mental workload on employees after the Covid-19 pandemic and provideinput to management for more effective workload distribution. The research results show the needfor additional training for supervisors and additional workforce in the Front Office area, such asreservations, drivers and security. Training is also needed for supervisors and staff in thehousekeeping area so that work becomes more efficient.